The Application of Manut (Muscle Nutrition Management) in the Elderly in Increasing the Degree of Health During the Covid-19 Pandemic in the Region of Medan Sunggal District - Eqlima; Girsang, Bina Melvia; Nurbaiti; Sitohang, Ance Marintan D (Talenta Publisher, 2022)
Nutrition is a top priority in determining the health of the elderly. Nutritional disorders in the elderly are often difficult to detect and require careful nutritional assessment One of the factors that influence it is nutritional care which has a positive effect on the energy intake of the elderly, so that the role of the elderly themselves is needed in maintaining their healthy quality. The purpose of this community service activity is to assess nutritional status and train the elderly in muscle nutrition management in the form of a book listing the activities carried out and their explanations. This activity was carried out on August 12, 2021 in the area of ​​​​the Medan Sunggal sub-district. These activities provide important benefits for the regulation of elderly nutrition and provide motivation that the elderly are able to make changes in healthy living behavior.